Generic regional aircraft flying qualities for the approach and landing task - Gautrey, Jim (Cranfield University, 1997)
Many changes have occurred in the past 20 years in aircraft manufacture and development. New technologies have appeared, spanning the entire aircraft design environment, such as new production methods, new materials and new avionics systems. These new methods have been developed for two reasons. For military aircraft, they have arisen through the need to improve performance. However, for civil aircraft they have arisen through the need to reduce the overall cost. This report considers one aspect of these technologies for civil aircraft: fly-by-wire. This technology uses electrical signalling in place of conventional heavy mechanical control runs. In addition, flyby- wire generally permits improvements to be made in aircraft flying and handling qualities. This requirement has originated from two main sources; a need to make improvements in the light of an increasing amount of experience, and a requirement to cope with aerodynamic modifications which have been implemented to improve aerodynamic efficiency, but which have a deleterious effect on the aircraft's flying and handling qualities. Both of these adverse effects have come about from a desire to reduce costs for the end aircraft user, i.e. the airlines. The aircraft used for these evaluations is a Generic Regional Aircraft, of about 100 seats and a weight of 90,000 lbs. Only a limited portion of the flight envelope was considered since these evaluations primarily concentrate on the approach and landing flight phase. These evaluations are being carried out as part of a joint Avro International Aerospace — Cranfield University Engineering Doctorate programme researching advanced flight control system design for a Generic Regional Aircraft. The overall aim of this programme is to produce a control law design which gives aircraft in question excellent handling qualities. The evaluations described here comprise the first in a series of three planned studies, and consider solely the approach and landing flight phase.